2020
DOI: 10.1016/s0140-6736(20)30801-1
|View full text |Cite
|
Sign up to set email alerts
|

Centring sexual and reproductive health and justice in the global COVID-19 response

Abstract: Global responses to the coronavirus disease 2019 (COVID19) pandemic are converging with pervasive, existing sexual and reproductive health and justice inequities to disproportionately impact the health, wellbeing, and economic stability of women, girls, and vulnerable populations. People whose human rights are least protected are likely to experience unique difficulties from COVID19. 1 Women, girls, and marginalised Centring sexual and reproductive health and justice in the global COVID-19 response unmonitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
200
1
31

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(241 citation statements)
references
References 11 publications
9
200
1
31
Order By: Relevance
“…In this context, the first retrospective case series published on a large cohort of consecutive patients with laboratory-confirmed SARS-CoV-2 referred for intensive care unit (ICU) admission to the coordination center of the SARS-CoV-2 in the ICU Network of the Lombardy region in Italy clearly depicted a dramatic snapshot: of 1591 patients, extraordinarily 1304 (82%) were males at the final follow-up at March 25, 2020 4 . Similar trends have also been reported in other countries 5 .…”
Section: Introductionsupporting
confidence: 90%
“…In this context, the first retrospective case series published on a large cohort of consecutive patients with laboratory-confirmed SARS-CoV-2 referred for intensive care unit (ICU) admission to the coordination center of the SARS-CoV-2 in the ICU Network of the Lombardy region in Italy clearly depicted a dramatic snapshot: of 1591 patients, extraordinarily 1304 (82%) were males at the final follow-up at March 25, 2020 4 . Similar trends have also been reported in other countries 5 .…”
Section: Introductionsupporting
confidence: 90%
“…The health [7], social [8,9], and economic [4,5,10] impacts of COVID-19 may interfere with the availability of nutritionally adequate and safe foods as well as the ability for people, including PLWH, to acquire food in socially acceptable ways. As indicated by reports of increasing food bank usage [24,25], it is reasonable to suggest that food insecurity among PLWH, along with its consequences (i.e., lower CD4 cell counts [37], incomplete HIV viral load suppression [38], and sub-optimal HIV treatment adherence [39]), may become more common.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the health [7] and social [8,9] impacts, the economic impacts of COVID-19, at both the micro-and macro-levels, have been unprecedented: long-standing businesses are shuttering [4,5], unemployment levels are climbing [10], and some countries are now reporting shrinking economies in Quarter 1, 2020 for the first time in more than a decade [11][12][13]. For example, in March 2020, Statistics Canada reported that more than one million jobs were lost in Canada, the worst single-month change on record [14].…”
mentioning
confidence: 99%
“…However, their situation is not known. Various studies have been conducted to understand the impact of the pandemic on people who are infected, other affected and vulnerable people, healthcare workers, etc since the inception of COVID-19 pandemic (for example, Armitage & Nellums, 2020;Banerjee et al, 2020;Hall et al, 2020;Kang et al, 2020;Kluge et al, 2020;Lima et al, 2020;Roy et al, 2020;Spoorthy, 2020;Wenham et al, 2020) but studies are limited on the transgender/hijra population. The present study gauges knowledge about COVID19, food insecurity, access to healthcare services, and psychological reactions of transgender/hijra population in Gujarat during COVID-19.…”
Section: Introductionmentioning
confidence: 99%